(untitled) (International Journal of Innovative Technologies in Economy, 2018)
The modern movement of trains in railway transport is a high-tech process related to the management of their movement through modern technical and information systems. The construction and modernization of these systems is cyclical and usually coincides with the rehabilitation and modernization of railway transport. These systems mainly employ mid and high management staff, namely traffic managers and train dispatchers of the respective railway sections. This publication discusses the contemporary aspects and perspectives for carrying out professional training and enhancing the qualifications of traffic managers and train dispatchers in railway transport. In fulfilling this objective, the functional characteristics, parameters and capabilities of the implemented concrete systems are taken into account, namely the company "TALES", which has implemented several projects in Bulgaria in recent years.